POLITICAL CORRUPTION AS A SYSTEM OF ILLEGAL ACTIONS: VARIABILITY OF ASPECTS - Мисишин, О. С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2021)
Theoretical and methodological bases of political corruption as a systemic problem are considered. Political corruption is analyzed as a complex political, socio-economic, legal phenomenon, its main features are studied, the main approaches to the interpretation of the concept of political corruption are systematized, the causes of corrupt economic relations are clarified. Emphasis is placed on the fact that political corruption is a specific element of the socio-political life of society and the state as a whole. It reduces the ability of public authorities to realistically and effectively solve various objectively arising social problems. The phenomenon of political corruption has a socio-global nature, mediated by a set of economic, political, socio-cultural factors of society. The conceptual consideration of this aspect of political corruption is based on the assertion that political corruption is a multilateral but holistic phenomenon. In other words, revealing political corruption in this aspect, it is necessary not only to identify its essential features in the framework of political, legal, socio-economic and socio-cultural approaches, but also to trace the relationship between them, to understand their combination in a single phenomenon. It turns out that the main mechanism of control of politicians, accountability to their voters are always civil society institutions, the absence of which, as well as the dependence of the legislative and judicial branches of government inevitably lead to political corruption, which in turn completes the cycle of political corruption. generates the production of such actions of the authorities.